Implementasi UU Nomor 10 Tahun 2009 Kepariwisataan Terhadap Minat Kunjung Wisatawan Ke Studio Alam Gamplong Yogyakarta - Nusanto, Tri Suyud; Yuliyantyo, Dedy Dwi; Alfira, Alfira (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This study aims to analyze the implementation of Law Number 10 of 2009 on Tourism with the increasing tourist interest in Studio Alam Gamplong, Yogyakarta. The research employs a normative juridical method supported by empirical data collected through document analysis, field observation, and interviews with 20 informants from government officials, tourism managers, business actors, and tourists. The findings show a 23% increase in tourist visits in 2023 and 68% community involvement in tourism management. However, regulatory gaps remain, particularly in technical provisions for visitor capacity and infrastructure support. A teleological interpretation of the law indicates that its objectives—improving community welfare and enhancing destination competitiveness—have not been fully realized. The study recommends the formulation of technical regulations at the regional level, the establishment of legally recognized tourism management institutions, and the optimization of local government roles in facilitation and promotion. These findings aim to strengthen legally grounded, sustainable, and participatory tourism policy governance.